Lipid‐Based Nanocarriers for The Treatment of Glioblastoma. Issue 2 (18th December 2020) - Iturrioz-Rodríguez, Nerea; Bertorelli, Rosalia; Ciofani, Gianni
Abstract : Glioblastoma multiforme (GBM) is the most common and malignant neoplasia having origin in the brain. The current treatments involve surgery, radiotherapy, and chemotherapy, being complete surgical resection the best option for the patient survival chances. However, in those cases where a complete removal is not possible, radiation and chemotherapy are applied. Herein, the main challenges of chemotherapy, and how they can be overcome with the help of nanomedicine, are approached. Natural pathways to cross the blood–brain barrier (BBB) are detailed, and different in vivo studies where these pathways are mimicked functionalizing the nanomaterial surface are shown. Later, lipid‐based nanocarriers, such as liposomes, solid lipid nanoparticles, and nanostructured lipid carriers, are presented. To finish, recent studies that have used lipid‐based nanosystems carrying not only therapeutic agents, yet also magnetic nanoparticles, are described. Although the advantages of using these types of nanosystems are explained, including their biocompatibility, the possibility of modifying their surface to enhance the cell targeting, and their intrinsic ability of BBB crossing, it is important to mention that research in this field is still at its early stage, and extensive preclinical and clinical investigations are mandatory in the close future. Abstract : Glioblastoma multiforme is one of the most common and malignant neoplasia that originates in the brain. Current therapeutic treatments own challenges that are overcome with the help of nanomedicine: for instance, lipid‐based nanocarriers are exploited to cross the blood–brain barrier and reach glioma cells, improving the therapeutic effects of chemotherapy drugs and decreasing their side effects.